Hambourg. Paradoxes et représentations contradictoires d’une métropole populaire - Samuel Depraz (Bulletin de l’Association de Géographes Français)
This contribution intends to study the metropolization process in Hamburg, taking in account the strong polycentrism of the German economy where several metropolis are competing for an international leadership. The public and private actors of the second biggest agglomeration of the country are striving for the rise of the upper economic functions of the city; they are carrying out ambitious urban renewal projects. A focus will be made on the consequences of those transformations on urban forms, and the gentrification process that is occurring at the same time in the city centre, led by the upper middle class and superior services. However, the popular and industrious trait of the port town of Hamburg makes original, violent reactions arise. Several local alternative groups are strongly rejecting the metropolization process, which is considered by to be ill-suited to the working-class identity of Hamburg.